Redefining Liver Fibrosis Risk Assessment in Indians with Type 2 Diabetes: New FIB-4 Score Cutoff for Optimizing Sequential Assessment with Transient Elastography - Rajat Deb; Soumik Goswami; Nilanjan Sengupta; Arjun Baidya; Vibhu R. Khare; Joydip Datta; Mousumi Das; Debes Ray (Indian Journal of Endocrinology and Metabolism)
Introduction: Liver fibrosis in metabolic dysfunction-associated steatotic liver disease (MASLD) is strongly related to hepatic and extrahepatic outcomes. Clinically Significant Liver Fibrosis (CSLF) screening using FIB-4 score is mandated in all T2D patients. The existing FIB-4 cutoff of 1.3 is derived from Western studies and could differ for Indians. Hence, we aimed to determine the FIB-4 cutoff to rule out Transient Elastography (TE) proven CSLF among Indians with T2D. Methods: 551 individuals with T2D underwent laboratory tests for FIB-4 calculation and transient elastography (TE) to detect CSLF defined as Liver Stiffness Measurement (LSM) ≥ 8kPa. The Receiver Operative Characteristic (ROC) curve was used to determine the optimum cutoff value of FIB4 to rule out CSLF. Results: 129 (23.4%) of 551 T2D patients in our cohort had CSLF. We found that a FIB-4 of 1.5 rules out CSLF with a sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and Diagnostic Accuracy (DA) of 82.9%, 79.9%, 55.7%, 93.8%, and 80.6%, respectively, compared with a FIB4 of 1.3 which has values of 91.5%, 67.3%, 46.1%, 96.2%, and 72.9%, respectively. Conclusion: A FIB-4 cutoff of 1.5 rather than 1.3 is suggested for Indian subjects with T2DM and needs to be validated in further large multicenter prospective studies, preferably with histopathology as the gold standard.